The association between autism symptom severity and parental marital satisfaction - Heyman, Sofie M., author; Lucas-Thompson, Rachel Graham, advisor; Harvey, Ashley, committee member; Rosén, Lee A., committee member (Colorado State University. Libraries, 2013)
Studies have suggested that parents of children with an Autism Spectrum Disorder (ASD) experience many stressors and a decrease in marital quality relative to parents of children without an ASD. Severity of the ASD symptoms have also been found to be associated with increased parenting stress and decreased social support, factors that predict decreases in marital quality. Associations between child autism symptom severity and parental marital quality were examined in the current study, and stress and social support were tested as potential mediators of that association. These associations were also compared for mothers and fathers. Parents with a child(ren) with an ASD (N = 18) were recruited through various different avenues and filled out surveys regarding marital quality, ASD symptom severity, levels of social support, and levels of parenting stress. Results suggested negative associations between child autism symptom severity and parental marital quality that did not appear to be mediated by stress or support. These findings suggest that parents who have a child with more severe symptoms are more likely to have poorer marital quality and there may be other mediators that help to explain the association. The marital quality of mothers also appeared to be more strongly and consistently associated with child symptom severity than fathers'. This study highlights the importance of further understanding how parents are affected in order to guide clinicians with how best to assist them.